2018
DOI: 10.3390/jcm8010029
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Oliguria with Decreased SvO2 Predicts Acute Kidney Injury after Living Donor Liver Transplantation

Abstract: Acute kidney injury (AKI) is a frequent complication after living donor liver transplantation (LDLT), and is associated with increased mortality. However, the association between intraoperative oliguria and the risk of AKI remains uncertain for LDLT. We sought to determine the association between intraoperative oliguria alone and oliguria coupled with hemodynamic derangement and the risk of AKI after LDLT. We evaluated the hemodynamic variables, including mean arterial pressure, cardiac index, and mixed venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…A post hoc analysis study of the RELIEF trial reported that oliguria, defined as urine output of less than 0.5 mL/kg/h, had a low predictive ability for postoperative AKI. Indeed, it was the absence of oliguria that demonstrated a good predictive ability of not developing postoperative AKI (34) . To enhance the predictive ability of oliguria, a study by Kim and colleagues suggests that intraoperative oliguria in combination with a decrease in SvO 2 can predict postoperative AKI more reliably than each of these factors alone, in a retrospective cohort of patients undergoing living donor liver transplantation (34) .…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis study of the RELIEF trial reported that oliguria, defined as urine output of less than 0.5 mL/kg/h, had a low predictive ability for postoperative AKI. Indeed, it was the absence of oliguria that demonstrated a good predictive ability of not developing postoperative AKI (34) . To enhance the predictive ability of oliguria, a study by Kim and colleagues suggests that intraoperative oliguria in combination with a decrease in SvO 2 can predict postoperative AKI more reliably than each of these factors alone, in a retrospective cohort of patients undergoing living donor liver transplantation (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Baseline graft parameters, including the incidence of a living/deceased donor and cold ischemic time, were significantly different between those with high and low mean DO 2 I groups. A deceased donor and cold ischemic time are reported to be associated with an increased risk of AKI [9,12,14,23]. A warm ischemic time of graft from donation after circulatory death is also associated with the severity of postoperative AKI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative hemodynamic variables have been investigated as modifiable risk factors in patients undergoing liver transplantation. Intraoperative arterial blood pressure, baseline central venous pressure, baseline right ventricular end-diastolic pressure and mixed venous oxygen saturation (SvO 2 ) during the anhepatic phase were reported to be associated with the development of posttransplant AKI [13,14]. Preoperative anemia and intraoperative transfusion amounts have also been reported as risk factors of AKI [9,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation is the most effective treatment for end-stage liver disease. AKI is a common complication following liver transplantation, which was found in 26.3%-75.6% patients, this disparity is large dependent on the definition of AKI [12,13,14]. [15,16].…”
Section: Discussionmentioning
confidence: 99%